PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 170 PEKANBARU - Oktariana Syamrosanti; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Basically the goal of education mathematic is to educate and the provide basic skill for students to self development according to their talents, interests, abilities and the environment, as well as a range of provision for students to continue their education to a higher level. The student’s mathematic outcomes at fourth grade in elementary school 170 Pekanbaru academic years 2013/2014 in the even semester is low. The purpose of this research is to increase the student’s mathematic outcomes by using cooperative Think Pair Share (TPS) learning model in the fourth grade in elementary school 170 Pekanbaru in the even semester academic 2013/2014, this research is action research class. The subject are fourth grade student’s elementary school 170 Pekanbaru that totally is 28 who is 14 male students and 14 female students. The students are heterogenic in academic. This research is three cycles, the data technique is observation and test. The percentage of the students before using the model is 46,4%, is increased 53,6% in the first cycle and increase 67,9% in the second cycle and increase also 85,7% in the third cycle. The activities of teacher and students has increased, the averager teacher’s activity in the first cyle is 60,94 with category enough increase 75,01 with categorygood in the second cycle and increase also 84,38 with category very good in the third cycle. The conclusion is shown that cooperative Think Pair Share (TPS) learning model can increase the student’s mathematic outcomes.Keywords: Think Pair Share (TPS), mathematic learning outcomes